Analisis Tekanan Seal pada Rudder Stock Menggunakan Computational Fluid Dynamics (CFD) - Wahyudi, Dedy; Coutsar, Ardan Nagra; Prasetyawati, Dian; Rizaly, Anastas (Pusat Riset dan Inovasi Nasional, 2025)
A ship is a type of floating structure that is specifically designed to move on the surface of sea water. This structure provides the ability for the ship to carry out various functions, from transporting goods, carrying passengers, to carrying out various other maritime operations. The advantage of a ship lies in its ability to move stably and efficiently in the midst of various dynamic marine environmental conditions. The direction of the ship's movement is controlled by the steering system, which is a crucial component in maintaining the smoothness and accuracy of the ship's journey. This steering system consists of various elements, one of which is the Rudder Stock. Rudder Stock has a vital role in the steering system because it functions as a link between the steering and the ship's propulsion system. Inside the Rudder Stock, there is another important component, namely the Seal. The Seal has the main function of withstanding pressure during ship operations, so that it can prevent leaks that can damage the steering system and other mechanical components. To evaluate the performance of the Seal in withstanding pressure, a pressure analysis was carried out using a numerical method based on Computational Fluid Dynamics (CFD) software, namely ANSYS. The results of the study showed that the total working pressure on the Rudder Stock Seal reached 0.766 bar, which is the sum of the maximum hydrostatic pressure of 0.432 bar and the maximum fluid flow pressure of 0.334 bar.